The health literacy level and its related factors in Iranian women with breast cancer undergoing chemotherapy - Sadeghian, Reyhaneh; Hamedani, Mahsa Asadollahi; Salehipour, Sajad; Sarabandi, Anahita; Kiani, Fatemeh; Babamohamadi, Hassan (Frontiers in Public Health, 2023)
Background Breast Cancer (BC) is the most common cause of female mortality throughout the world. Promoting public awareness about this disease is the most crucial method of its prevention or control. The present study was carried out to determine the health literacy level and its related factors in women with BC. Methods This cross-sectional study was conducted on BC patients undergoing chemotherapy in two teaching hospitals affiliated to Zahedan University of Medical Sciences in 2020. A total of 210 patients referred to these chemotherapy centers were selected by purposive sampling. The data collection tools included a demographic information form and a health literacy questionnaire for Iranian women with BC. The collected data were analyzed using descriptive and inferential statistics (logistic regression) in SPSS-22. p-values less than 0.05 were considered statistically significant. Results The mean total score of the health literacy of women with BC undergoing chemotherapy was 40.35 ± 19.01, which suggests an insufficient health literacy. The health literacy had a significant relationship with variables including university education (OR = 4.41, p = 0.005) and supplementary insurance coverage (OR = 5.83, p < 0.001). Conclusion The findings showed that university education and supplementary insurance coverage are associated with a higher health literacy among women with BC. Improving these factors and paying further attention to their role in the promotion of health literacy can help enhance the health literacy of women with BC.